Osteology and neuroanatomy of a phasianid (Aves: Galliformes) from the Miocene of Nebraska. (January 2023) - Ksepka, Daniel T.; Early, Catherine M.; Dzikiewicz, Kate; Balanoff, Amy M.
Abstract: Tetraoninae (grouse) and Meleagridinae (turkeys) are conspicuous representatives of the modern North American avifauna. The pre-Pleistocene fossil record of these clades has historically been limited to fragmentary remains, in some cases contributing to confusion rather than improving our understanding of how these charismatic landfowl evolved. We report an exquisitely preserved partial skeleton representing a new species of Late Miocene phasianid from the Ash Hollow Formation of Nebraska. Centuriavis lioae n. gen. n. sp. is a phasianid species close in size to modern sage-grouse that diverged prior to the grouse-turkey split, and thus offers insight into the early history of this radiation. The cranial endocast resembles other North American phasianids and differs from odontophorids in exhibiting a strongly projected Wulst bordered by a well-defined vallecula. Phylogenetic analyses indicate that Centuriavis lioae forms a clade with Tetraoninae, Meleagridinae, and Pucrasia macrolopha (Koklass pheasant). The new fossil species provides a Late Miocene minimum calibration for the divergence of these extant taxa from other Galliformes and supports the hypothesis of a single dispersal from Asia to North America by a lineage that later gave rise to grouse and turkeys. UUID: https://zoobank.org/34ecda2f-f2f2-4c92-a82f-292e23cf2da1